“O nome de Deus e o novo governo”: a questão da secularização do Estado na imprensa metodista (1886-1891) - Silva, Rodrigo Henrique Ferreira da (2021)
In this research we seek to analyze the view of the Methodist Church in Brazil on the process of secularization of the Brazilian State between the final years of the Empire and the beginning of the Republican Period (1886-1891), a period marked by institutional separation. between the State and the Catholic Church, institutions united since the beginning of Portuguese colonization by the Padroado regime. To do so, it will focus on two distinct moments: first in the debates and the Methodist effort for the end of the Padroado system and for the institutional separation between the Catholic Church and the State in the final years of the Empire (1886- 1889) and then, in the struggle for consolidation of secularization, which extends to the promulgation of the Constitution of 1891. It is intended, therefore, to understand how the missionaries of the aforementioned Church understood the relations between the State and religions, as well as how they acted to ensure the institutional separation between the publicpolitical and religious spheres, a process here called secularization, and which was considered essential by Methodist missionaries for the development of their Church. For this purpose, we take as our main source the periodicals published by the Methodist Church during this period, namely the Methodista Catholico and the Expositor Christão. We defend here that the Methodists sought to implant in Brazil a kind of State/religion relationship inspired by the North American model of secularization. This model is marked by the separation between the State and religious institutions, but at the same time by the presence of numerous religious references of Judeo-Christian origin in the public and political sphere